Study of chronic renal disease in canine and geriatric felines - González-Castillo, Luis Felipe; Sanmiguel-Plazas, Rosa Angélica (Universidad Pedagógica y Tecnológica de Colombia, 2018)
This paper seeks to compile updated aspects related to Chronic Kidney Disease (CKD) both in geriatric canines and cats. Worldwide this disease affects 0.5–1.5% of canines and 1–3% of cats, with mortality rates of 5% and 3%, respectively. The literature review provides updated information on different aspects of the pathology. CKD affects canines and cats mainly of advanced age and is characterized by renal hypofunction, which, over time, leads to persistent abnormalities, mostly irreversible (azotemia and inability to concentrate urine), generating in the patient a multisystem toxic syndrome that besides altering the efficiency of the kidneys, affects other systems in an integrated manner. Unlike human medicine, current tools for diagnosis, treatment, prevention and control for CKD in canines and cats are limited due to their elevated costs and the difficulty acquiring specialized equipment; this situation prevents patients from receiving procedures that can benefit their quality of life.